The Variation of Functional Traits in Leaves and Current-Year Twigs of Quercus aquifolioides Along an Altitudinal Gradient in Southeastern Tibet - Zhang, Xinsheng; Wang, Chao; Zhou, Chenni (Frontiers in Ecology and Evolution, 2022)
Clarifying the adaptation mechanism of alpine plants to climate or habitat under the alpine environmental gradient on the Qinghai–Tibet Plateau is substantially important to understand the their geography in alpine regions and their responses to future climate change. The spatial distribution characteristics of functional traits in leaves and current-year twigs of Quercus aquifolioides on five consecutive altitudinal gradients in Southeastern Tibet were analyzed. The relationship between the functional traits and habitat factors (topographic and soil factors) was explored. Key results: the functional traits of leaves and current-year twigs of Quercus aquifolioides in Southeastern Tibet showed significant linear variations along the altitudinal gradients (p < 0.001). Quercus aquifolioides at low altitudes tended to have shorter current-year twigs and less leaves with larger LA (leaf area) and higher RWC (relative water content) than those at high altitudes. Strong trade-off and coordination relationship were found between the functional traits of leaves and those of current-year twigs, respectively. SL (slope) and TN (total nitrogen) contributed the most to leaf functional traits (p < 0.05); AL (altitude) was the main determinant of functional traits in current-year twigs of Quercus aquifolioides in southeast Tibet. In conclusion, our observation demonstrate that the ecological adaptation strategy of Quercus aquifolioides was formed through the trade-off mechanism among various functional traits, the variation of hydrothermal conditions and soil environmental factors caused by altitude in the alpine region lead to differences in functional traits of Quercus aquifolioides along an altitudinal gradient in southeast Tibet.